Estrategias para lograr ahorro energético en el Hospital San Rafael de Alajuela - Vásquez-Rodríguez, Rosa Elena (Instituto Tecnológico de Costa Rica, 2012)
This project has been executed in the San Rafael of Alajuela Hospital in response of the necessity of the medical center as well as of the Caja Costarricense de Seguro Social to save the resources available and to promote the initiatives of the government regarding the National Strategy of Climate Change and to reach the national goal of Carbon Neutrality for the year 2021 To accomplish this it has been proposed to improve the energy efficiency of the San Rafael Hospital. In first place it was establish the necessity to evaluate the energy situation in the Hospital. Thanks to this evaluation it was determined that the Hospital consumed in the 2011 an average of 43,83 kWh/bed/day and when comparing with the year 2009, that was the established base year, there was a reduction of consumption of 6,09 kWh/bed/day, which equates to a daily saving of ¢ 171.843,44. Moreover, it was determined the distribution of consumption of the Hospital, which indicates that the air conditioning service represents the 38% of the electric consumption and that the illumination of the medical center represents the 32% of the consumption. From these results the second objective was established: to design methods of energy saving and to train the personnel. In regards to the air conditioning system, the increase of the temperature of the set point was evaluated at 1°F, expecting that this would result in a reduction of the consumption in an important manner. However, the measurements of the consumption where conduct on a short time and the results did not indicate a specific saving. As part of the savings measures in illumination the installation of timers was assessed in the external consult area, obtaining as a result that the investment could be returned in 3 years and collecting a $990 saving. Furthermore, the substitution of bulbs for lamps of less consumption than the current was assessed, and it was estimated a monthly saving of 4 million colons. It is important to mention that the replacement of the lamps will be implemented when XV each unit ends its cycle, so this savings won’t be tangible until the substitution is completed. Finally, answering to the Hospitals initiatives in the protection of the environment, the installation of solar powered water heaters was assessed in order to reduce the consumption of LP gas. It was determined that in a 4 year period the investment could be recovered. However, due to the lack of real data of consumption of hot water and of gas from the Hospital, it was not possible to conduct correct calculation. A photovoltaic system was also assessed for the Hospital. It was proposed a system that would cover 10% of the consumption, with a cost of $s1.020.000,00. This equipment would pay itself through saving in a 10 year period. However, it was no possible to evaluate in detail this proposal due to the lack of cost estimates from distributors for the system.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2012.
Keywords: Eficiencia; Consumo de energía; Suministro de energía eléctrica; Distribución de energía eléctrica; Ahorro energético; Protección del medio ambiente